2012
DOI: 10.3171/2011.12.focus11323
|View full text |Cite
|
Sign up to set email alerts
|

Curative Onyx embolization of tentorial dural arteriovenous fistulas

Abstract: Object The authors conducted a study to review their experience with tentorial dural arteriovenous fistulas (DAVFs) treated with transarterial endovascular embolization in which Onyx was used. Methods The authors reviewed prospectively collected data in 9 patients with tentorial DAVFs treated with Onyx embolization between 2008 and 2011. Information reviewed included clinical presentation, angiographic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 17 publications
1
17
0
13
Order By: Relevance
“…With the advent of newer embolic agents (Onyx, Covidien), we have been able to safely and effectively obliterate many tentorial DAVFs. 12 In our experience, a sine qua non for successful embolization is the presence of a well-developed posterior branch of the middle meningeal artery supplying the lesion. This branch is relatively straight and allows distal catheterization, which in turn increases the likelihood of penetration of the embolic agent well into the proximal draining vein.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of newer embolic agents (Onyx, Covidien), we have been able to safely and effectively obliterate many tentorial DAVFs. 12 In our experience, a sine qua non for successful embolization is the presence of a well-developed posterior branch of the middle meningeal artery supplying the lesion. This branch is relatively straight and allows distal catheterization, which in turn increases the likelihood of penetration of the embolic agent well into the proximal draining vein.…”
Section: Discussionmentioning
confidence: 99%
“…The occipital artery, the second most likely artery to supply a dAVF in this series, follows a more tortuous, transosseous course which inhibits microcatheter access, navigation, and Onyx penetration. The same is true for a number of other tributaries of other branches of the external carotid, internal carotid, and vertebral arteries that supply dAVFs including the posterior middle meningeal artery, another branch that frequently supplies dAVF of the posterior cranial fossa and tentorium cerebelli and incisura (Puffer et al, ). However, the tortuosity of the posterior meningeal artery after initial take off from the vertebral artery frequently precludes distal catheterization.…”
Section: Discussionmentioning
confidence: 96%
“…Although proximal Onyx reflux may occur with a high margin of safety in the middle meningeal artery, reflux should not be allowed in proximity to the level of the foramenspinosumtoavoidinadvertentcompromiseofthearterialsupplyto the trigeminal and facial nerves. 16 Even though we have attempted to summarize data on all published series of treated TDAVFs, our study has certain limitations. The results of separate case series were published by multiple authors who reported independently assessed data and who determined different specific variables that are included in this article.…”
Section: Discussionmentioning
confidence: 99%